Ordering pH‐Responsive Polyelectrolyte‐Grafted Nanoparticles in a Flow Coating Process. Issue 5 (9th January 2018) - Zhang, Chongfeng; Carlson, Thomas; Yang, Siyang; Akcora, Pinar
Abstract: The effects of nanoscale particle interactions on deposition patterns in the flow coating process are investigated using pH‐responsive poly(acrylic acid) (PAA)‐grafted silica nanoparticles. Interactions between nanoparticles are effectively controlled by grafting densities, PAA brush lengths, and pH, in addition to hydrogen bonding between free polyvinylpyrrolidone (PVP) and PAA. Consequently, various intriguing patterns of randomly distributed dots, polygonal networks, meshes, fork‐like structures along with highly regulated and densely packed stripes parallel to the moving direction of substrates are fabricated. Per se, the flow coating process is shown to form regulated patterns during evaporation by controlling particle–particle interactions with inherent brush properties and external pH. Abstract : Various intriguing patterns of nanoparticles are fabricated in a flow coating process by utilizing hydrogen bonding between poly(acrylic acid)‐grafted silica nanoparticles and free polyvinylpyrrolidone and altering brush conformations with pH.